Prototipe Penilaian Kinerja Tenaga Ahli PT. Inacon Luhur Pertiwi Dengan Pendekatan Adaptive Neuro Fuzzy Inference System (ANFIS) - Handa Gustiawan (Jurnal Teknologi Informatika & Komputer)
Inacon Luhur pertiwi PT. as a management consulting firm in carrying out its work on the project PNPM Urban with contract number HK.02.03 / NMC / IBRD / SATKER-PK / 007/2012 dated 10 May 2012. By carrying out quantitative research methods, using primary and secondary data as samples. Primary data retrieved by conducting an observation as an observation instrument of experts performance assessment. Secondary data was collected by observing the data, reading, studying and quoting from the book of literature, as well as the resources that are closely related to this study. The data obtained will be used for purposes of descriptive data analysis process by using Adaptive Neuro Fuzzy Inference System (ANFIS). ANFIS method is a method that uses neural networks to implement fuzzy inference system. Fuzzy inference system used is the fuzzy inference system models Tagaki-Sugeno-Kang (TSK) with consideration of simplicity and easy computation. The result of this research is the prototipe of expert performance evaluation which can be implemented at Inacon Luhur Pertiwi PT.